Penerapan Pasal 1 ayat (2) Kitab Undang-Undang Hukum Pidana dalam Perspektif Kontemporer - Yuvens, Damian Agata (Jurnal Konstitusi, 2016)
Article 1 paragraph (2) Indonesian Criminal Code is an article designed as bridge between the old and new criminal provisions. Recalling the “age” of Article 1 paragraph (2) Indonesian Criminal Code that is so old, there is an urgency to conduct analysis in contemporary perspective whether or not Article 1 paragraph (2) Indonesian Criminal Code can be implemented under the current law regime in Indonesia. In implementing Article 1 paragraph (2) Indonesian Criminal Code, elements that shall be regarded are: (i) defendant; (ii) change of laws and regulations after the crime is committed; (iii) most favourable provision. There should be an adjustment on the method of interpreting both elements of defendant and change of law and regulations; on the other hand, there must be a case-by-case study to answer the element of most favourable provision. Aside from elements of Article 1 paragraph (2) Indonesian Criminal Code, there should also be a consideration on transitional provisions of the changed law to determine whether or not Article 1 paragraph (2) Indonesian Criminal Code could be implemented.